2020
DOI: 10.1186/s12936-020-03382-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of malaria infection among children of local farmers in Central Malawi

Abstract: Background: Malaria is a leading cause of morbidity and mortality among children under 5 years in Malawi, and especially among those from rural areas of central Malawi. The goal of this study was to examine the prevalence and determinants of malaria infection among children in rural areas of Dowa district in central Malawi. Methods: A multistage, cross-sectional study design was used to systematically sample 523 child-mother dyads from postnatal clinics. A survey was administered to mothers and a rapid malaria… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 41 publications
2
27
1
Order By: Relevance
“…older children [34][35][36]. Findings also show that the higher the level of a mother's education, the lower the prevalence of malaria among under-five children.…”
Section: Plos Onementioning
confidence: 83%
See 2 more Smart Citations
“…older children [34][35][36]. Findings also show that the higher the level of a mother's education, the lower the prevalence of malaria among under-five children.…”
Section: Plos Onementioning
confidence: 83%
“…First, younger children may be protected from malaria because of the antibodies they acquire from their mother during pregnancy and during breastfeeding [ 33 ]. Second, younger children in some countries in sub-Saharan Africa, including DRC, share a bed with their mother and are more likely to be covered properly with a blanket or an ITN than older children [ 34 36 ]. Fig 3 shows the proportion of under-five children who slept under an ITN the night preceding the study by age in DRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with the literature in SSA that found that marital infidelity by men was a significant trigger of IPV against women [ 1 , 49 ]. Studies have shown that when women confront their partners after discovering their infidelity, some partners respond aggressively, which can escalate into emotional or physical violence [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the nexus between COVID-19 measures and food security in the Malawian context is crucial for effective implementation of interventions that can help reduce the risk of being food insecure while preventing further spread of the virus. Food insecurity is linked to child stunting and this is a big problem in Malawi as evidenced in the central region (Chilanga, 2020). However, there is gulf in knowledge of how COVID-19 policy measures have led to urban food insecurity among urban residents in Malawi.…”
Section: Introductionmentioning
confidence: 99%